FROM BAGONG TO MBAPPÉ: CULTURAL REPRESENTATION AND MYTH IN ROLAND BARTHES' SEMIOTIC PERSPECTIVE - Joko Susilo; Endang Sriwahyuni; Moh Atikurrahman; Indra Tjahyadi (Journal of Social Science, 2026)
Objective: This study examines the representations of innocence, sincerity, and wholehearted commitment embodied by the character of Bagong in the Bagong Gendro shadow puppet performance and the playing behavior of Kylian Mbappé through the lens of Roland Barthes' semiotic theory. Method: Employing a qualitative research approach, the study applies Barthes' three levels of semiotic analysis: denotation, connotation, and myth. The primary data consist of documentation of the Bagong Gendro wayang kulit performance and audiovisual recordings of Kylian Mbappé's performances in football matches. Results: The findings reveal that Bagong represents innocence, honesty, and sincerity as forms of moral strength, whereas Mbappé embodies commitment, professionalism, and dedication in pursuing collective goals. At the level of myth, both representations construct the understanding that success is determined not merely by individual ability but also by integrity, consistency, and genuine commitment in fulfilling one's role. This study demonstrates that the local cultural values embodied in the character of Bagong can engage in dialogue with the global values of professionalism represented by a modern sports figure, thereby offering a reflection on the cultural identity of the Nusantara people within an international context. Novelty: This study comparatively analyzes the symbolic representations of Bagong and Kylian Mbappé through Roland Barthes' semiotic framework, connecting local cultural values with global professional ethics.